La città-rifugio: una declinazione dell'accoglienza tra solidarietà e autonomia - Furri, Filippo (2018)
The relation between migration and the city – the urban space and his population – is constantly evolving, and is conditioned by specific political, geographical and historical factors. Nevertheless, over the last decades, due to the differential access to human mobility and in contrast with an increasing demand for this mobility for different reasons, the idea of foreigner, of migrant, has been changing. Faced with an identity “immunitarian” withdrawal, based on the paradigms of nationality and citizenship, different solutions of cohabitation and interaction have been progressively configured. In particular, in the local scape the notion of City of Refuge is oriented around solidarity and autonomy.